Quality Cancer Care Survivorship Before, During and After Treatment (Springer International Publishing, 2018)
This book follows the continuum of cancer care model as its outline vide infra. As cancer is now a very multidisciplinary disease, it encourages dedicated professionals from various specialties as well as active patient cooperation in order to improve successful treatment and survival. This text will serve as a detailed reference source for healthcare providers intending to improve the quality of survivorship of cancer patients, as well as help create affordable care plans. Initially it discusses the current cancer care crisis on a global and then national platform. Chapters include discussions about disability adjusted life years lost, lost productivity, loss of life and its impact upon the nation and communities. In order to deescalate the financial impact of cancer on society and government, this text incorporates smarter and efficient treatment alternatives that will also improve the survivorship of patients, families and caregivers. It also illustrates how prevention and screening programs can be incorporated to improve cancer care. Quality Cancer Care: Survivorship Before, During and After Treatment will become an invaluable resource for healthcare professionals and clinical staff involved in the delivery of cancer care. .